A survey of the possible curriculum materials in the primary grades in certain schools in Manila - Maceda, Trinidad S. 1913- ([Quezon City University of the Philippines], 1954)
This study surveys the curriculum materials that can be suited to the child's interests and needs and therefore in accord with the present curricular trends. It also identifies the materials that may be utilized to enrich and/or revise the primary curriculum.
Bibliography: p. 226-227.
Thesis (M.Ed.)--University of the Philippines, 1954
Typewritten
Vita